Biological Function of Long Non-coding RNA (LncRNA) Xist - Wang, Wenlun; Min, Lu; Qiu, Xinyuan; Wu, Xiaomin; Liu, Chuanyang; Ma, Jiaxin; Zhang, Dongyi; Zhu, Lingyun (Frontiers in Cell and Developmental Biology, 2021)
long non-coding RNAs (lncRNAs), which are transcribed from the mammalian genome as long transcripts with sizes greater than 200 nt in length and lacked protein-coding potential, primarily regulate gene expression at epigenetic, chromatin remodeling, transcriptional, and translational levels in variety of ways. Accumulating evidence suggests that lncRNA X-inactive specific transcript (lncRNA Xist) is emerging as important regulators of cell growth and development. LncRNA Xist not only plays critical roles in X-chromosome dosage compensation though inducing heterochromatinization of the X-chromosome by recruiting repressive protein complexes to chromatin, but also participates in tumor and non-cancer disease development by functioning as a competing endogenous RNA (ceRNA). In this review, we summarized recent progress from studies in cellular functions of lncRNA Xist in mammalian cell, and discussed current knowledge regarding the ceRNA network of lncRNA Xist in various diseases.